Chemical composition of Ivorian Artabotrys insignis leaf oil. Combined analysis including 13C NMR, to quantify germacrene A and β-elemene. Issue 15 (3rd August 2017) - Gooré, Stéphane G.; Ouattara, Zana A.; Yapi, Thierry A.; Békro, Yves-Alain; Tomi, Pierre; Paoli, Mathieu; Tomi, Félix
Abstract: The chemical composition of leaf essential oil from Artabotrys insignis Engler & Diels collected from Cote d'Ivoire was determined by GC(FID), GC-MS and 13 C NMR. The main compounds were β-elemene (66.8%) and germacrene A (17.1%). The true content of germacrene A/β-elemene was obtained by combining GC(FID) and 13 C NMR data. Abstract :